2017
DOI: 10.3390/medicines4030052
|View full text |Cite
|
Sign up to set email alerts
|

β-Selinene-Rich Essential Oils from the Parts of Callicarpa macrophylla and Their Antioxidant and Pharmacological Activities

Abstract: Background: Callicarpa macrophylla (Varbenaceae) is a medicinal shrub and is traditionally used in India, China, and South Asia. Methods: The plant material was collected from lower Himalayan region of Uttarakhand in India. The essential oils from three different aerial parts were analyzed by GC-MS. Antioxidant activity, phenolic assay, and various pharmacological activities were determined by using existing methods which are generally practiced widely. Results: Over 51, 53, and 40 compounds were identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…Moreover, E -caryophyllene is one of the major compounds in several essential oils, having positive effects by reducing inflammation, acute pain, and chronic pain as well as regulating insulin secretion [ 26 , 27 , 28 ]. β -selinene is found in various essential oils, including PEO; an oil enriched with β -selinene shows anti-inflammatory and pain relief effects as well as lowering body temperature, in addition to being a powerful antioxidant [ 29 ]. Tsuji et al [ 30 ] reported that inhalation of limonene, a primary compound in grapefruit oil, elicits hypoglycemic effects.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, E -caryophyllene is one of the major compounds in several essential oils, having positive effects by reducing inflammation, acute pain, and chronic pain as well as regulating insulin secretion [ 26 , 27 , 28 ]. β -selinene is found in various essential oils, including PEO; an oil enriched with β -selinene shows anti-inflammatory and pain relief effects as well as lowering body temperature, in addition to being a powerful antioxidant [ 29 ]. Tsuji et al [ 30 ] reported that inhalation of limonene, a primary compound in grapefruit oil, elicits hypoglycemic effects.…”
Section: Resultsmentioning
confidence: 99%
“… 2017 ; Chandra et al. 2017 ). This suggests that PFPE may help to reduce the cytotoxic effect and pro-inflammatory response of Dox through anti-oxidative and anti-inflammatory capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The genus of Callicarpa consists about 140 species that are distributed mostly in Oceania and east and southeast Asia including India, Myanmar, Thailand, and Vietnam [1][2][3], of which, several species such as Callicarpa candicans, C. americana L., C. japonica, C. macrophylla, and C. longissimi are highly valued for their essential oils, which are rich in terpenoids, phenylethanoids, volatile oils, lignans, and flavonoids. These classes have been known for a wide range of biological activities including antimicrobial, analgesic, antipyretic, anti-inflammatory, and anti-infection [2,[4][5][6][7]. C. candicans (Burm.…”
Section: Introductionmentioning
confidence: 99%